Konsep Pemanfaatan Ruang Terbuka Di Kawasan Kota Lama Semarang - Ardiana Yuli Puspitasari; Jamilla Kautsary (Jurnal Planologi, 2020)
ABSTRACTMorphologically, the Semarang Old Town area has a very important role in the development of Semarang City and also has an important value for the development of urban area planning science. One urban element that has an important role in influencing the quality of the environment is the presence of green open spaces and non-green open spaces. The existence of open space as an inseparable part of buildings and historic environment in the Old City Region of Semarang provides space as a place of activity for the community and visitors. The objective to be achieved is to identify the potential use of open space in the Old City Region as a basis for designing the fulfillment of the availability of open space in this region, given the potential for tourism activities that continue to develop. This research approach uses qualitative descriptive empirical analysis methods. The results of this study are open space available in the old city at 18% of the core area of the old city and mostly in the form of road corridors (34%). Open space in the core area of the old city is still much that can be developed to accommodate the activities of visitors because until now the activity in the open space is still concentrated in the area of Taman Srigunting and Gereja Blenduk. The concept of open space utilization is directed at the river Kali Semarang area (riverfront) because in that area it still has great potential to be developed. The conclusion of this study is that the potential for open space utilization in the core area of the old city is still very large to facilitate the development of tourist activity which is increasing, so it is necessary to spread the gathering point of activities so that it is not concentrated in the area of the Taman Srigunting and Gereja Blendukg. The concept offered is riverfront open space along Semarang River.Keywords: concept, utilization, open space ABSTRAKSecara morfologi, kawasan Kota Lama Semarang memiliki peran yang sangat penting terhadap perkembangan Kota Semarang dan juga memiliki nilai penting bagi perkembangan ilmu perencanaan wilayah kota. Salah satu elemen perkotaan yang memiliki peran penting dalam mempengaruhi kualitas lingkungannya adalah keberaaan ruang terbuka hijau dan ruang terbuka non hijau. Keberadaan ruang terbuka sebagai bagian yang tidak terlepaskan dari bangunan dan lingkungan bersejarah di Kawasan Kota Lama Semarang memberikan ruang sebagai wadah aktivitas bagi masyarakat dan pengunjung. Tujuan yang ingin dicapai yaitu teridentifikasi potensi pemanfataan ruang terbuka di Kawasan Kota Lama sebagai dasar untuk merancang pemenuhan ketersediaan ruang terbuka di kawasan ini, mengingat potensi kegiatan wisata yang terus berkembang. Pendekatan penelitan ini menggunakan kualitatif dengan metode analisis deskriptif empirik. Hasil dari penelitian ini adalah ruang terbuka yang tersedia di kota lama sebesar 18% dari luas kawasan inti kota lama dan sebagian besar berupa koridor jalan (34%). Ruang terbuka di kawasan inti kota lama masih banyak yang bisa dikembangkan untuk mewadahi aktivitas pengunjung karena sampai saat ini aktivitas pada ruang terbuka masih terpusat di area taman srigunting dan gereja blenduk. Konsep pemanfaatan ruang terbuka diarahkan pada  area sungai Kali Semarang (riverfront) karena pada area tersebut masih memiliki potensi yang besar untuk dikembangkan. Kesimpulan penelitian ini adalah potensi pemanfaatan ruang terbuka di kawasan inti kota lama masih sangat besar untuk mewadahi perkembangan aktivitas wisatawan yang semakin meningkat, sehingga perlu persebaran titik kumpul aktivitas agar tidak memusat di area taman srigunting dan gereja blenduk. Konsep yang ditawarkan adalah riverfront open space di sepanjang Kali Semarang.Kata kunci: konsep, pemanfaatan, ruang terbuka